Mečislovas Reinys’ Pedagogical Ideas in Today’s Moral Education Programmes - Pipiras, Nerijus (Jaunųjų mokslininkų darbai, 2019)
The Thomas Groome model, used to prepare moral (religious) education programmes for Lithuanian primary and basic schools, has been presented in the paper. In this model, Christian values have been dealt with by solving life problems. The main purpose of moral education is to develop various skills: to make decisions, to take responsibility for one’s own development and learning, to draw considered conclusions coping with the problems of the time. Values should not be separated from life. On the contrary, we should bear them in mind solving our problems. A broad, holistic approach is necessary.The purpose of moral education is to equip children with moral values, moral education is an interdisciplinary process. Archbishop Mečislovas Reinys, one of the most intellectual personalities in the interwar period, emphasized that.Several Archbishop M. Reinys’ articles, in which he analyzed the importance of education and the development of the whole person, have been discussed in the second part of the article. He published his thoughts on the importance of education for human development in science journals and periodicals after his return to Lithuania from studies abroad.
Keywords: Archbishop; moral education; programmes